Deixis in the Lyrics of "Happier" by Olivia Rodrigo - Risanty, Cindy Avika; Prasetyo, Yudy; Rio, Henry; Aisyah, Siti (Journal of English Language and Education, 2025)
This study explores the use of deixis in Olivia Rodrigo's song "Happier." It examines how deixis constructs emotional meaning and narrative coherence through linguistic elements. The focus is on identifying and analyzing five types of deixis: person, temporal, spatial, social, and discourse. This analysis interprets how language operates pragmatically within the song. Using a qualitative descriptive method, the research applies Levinson's framework for a detailed textual analysis. The song was selected purposively due to its emotional depth and linguistic richness. The findings reveal that person deixis is the most dominant type. It reflects the narrator's shifting emotional position toward her ex-partner and his new relationship. Temporal deixis marks the emotional timeline of the breakup. Meanwhile, spatial deixis subtly conveys psychological distance. Social deixis uncovers power dynamics and feelings of inferiority. Discourse deixis helps maintain the coherence of the emotional narrative. Each type of deixis contributes to building a layered and affective discourse that enhances the song's emotional resonance. The study concludes that deixis functions not only as a grammatical tool but also as an expressive and narrative device in popular music. The song "Happier" exemplifies how deixis can encode emotional complexity. This makes it a useful medium for both linguistic analysis and language learning. The research recommends further studies on deixis in multiple songs to gain broader insights into its stylistic and pragmatic functions.